Oikonomia, Incarnation and Immediacy: The Figure of the Jew in St John of Damascus. Issue 3 (27th May 2017) - Benjamin, Andrew
Abstract: This paper investigates the role of oikonomia in the writings of St John of Damascus and how that role is integral to the construction of the figure of the Jew.